2016
DOI: 10.18393/ejss.2016.4.266-274
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cation exchange capacity and soil water holding capacity from basic soil properties

Abstract: Cation exchange capacity (CEC) is a good indicator of soil productivity and is useful for making recommendations of phosphorus, potassium, and magnesium for soils of different textures. Soil water holding capacity (SWHC) defines the ability of a soil to hold water at a particular time of the season. This research predicted CEC and SWHC of soils using pedotransfer models developed (using Minitab 17 statistical software) from basic soil properties (Sand(S), Clay(C), soil pH, soil organic carbon (SOC)) and verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
4
21
0
1
Order By: Relevance
“…The correlation between % sand and % clay agrees with the results of Coffin and Lauenroth (1992), Kaiser et al (1992), and Pan et al (2012). Negative correlation between % sand and MC is in line with similar results by Senjobi and Ogunkunle (2011) and Olorunfemi et al (2016). The strong negative correlation between % sand and ALs agrees with similar results by Deng et al (2017) and Igwe et al (2013), while correlation between % sand and PI (− 1.000**) is in line with similar result by Roy and Bhalla (2017) who reported that increase in sand content results in decreased PI.…”
Section: Results Of Statistical Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…The correlation between % sand and % clay agrees with the results of Coffin and Lauenroth (1992), Kaiser et al (1992), and Pan et al (2012). Negative correlation between % sand and MC is in line with similar results by Senjobi and Ogunkunle (2011) and Olorunfemi et al (2016). The strong negative correlation between % sand and ALs agrees with similar results by Deng et al (2017) and Igwe et al (2013), while correlation between % sand and PI (− 1.000**) is in line with similar result by Roy and Bhalla (2017) who reported that increase in sand content results in decreased PI.…”
Section: Results Of Statistical Analysessupporting
confidence: 91%
“…This buttressed the fact that the higher the fine particles (clay), the higher the MC but lower the DD (Dave et al 2017). However, negative correlation found between CEC and % clay is in contrast with positive correlation between % clay and CEC found earlier by Lambooy (1984) and Olorunfemi et al (2016). This may be due to low MC and high sand content of analysed soil samples.…”
Section: Results Of Statistical Analysesmentioning
confidence: 74%
“…Available sulfur was determined by the turbidimetric method [21]. Exchangeable potassium (K + ) and sodium (Na + ) were determined by flame photometry [22] while exchangeable magnesium (Mg 2+ ) and calcium (Ca 2+ ) were determined by atomic absorption spectrophotometer [23]. Cation exchange capacity (CEC) was measured by ammonium acetate (NH 4 OAc at pH 7.0) method [24].…”
Section: Analysis Of Physicochemical Propertiesmentioning
confidence: 99%
“…The consistency of PTFs is mainly dependent on the number of samples and range of the input parameters (Chirico et al, 2010). Pedotransfer functions for CEC are often developed from a combination of different properties (e.g., clay content, organic C [OC] content, and hygroscopic water content) (Arthur, 2017; Krogh et al, 2000; McBratney et al, 2002; Olorunfemi et al, 2016; Torrent et al, 2015). For instance, Krogh et al (2000) showed that a PTF based on clay and OM contents dominated by illite reliably explained 90% of the variability in CEC for Danish soils.…”
mentioning
confidence: 99%